Subchronic nonylphenol exposure induced anxiety-like behavior and decreased expressions of regulators of synaptic plasticity in rats. (November 2021) - Li, Shengnan; Xu, Weihong; Gong, Lei; Zhang, Jianling; Zhang, Yujie; Chen, Jingting; Yu, Jie; Xu, Jie
Abstract: Studies have shown that there were associations between endocrine disrupting chemicals (EDCs) and anxiety. Nonylphenol (NP) is an EDC with weak estrogen activity. This study aimed to clarify whether subchronic exposure of NP at environmental concentrations induces anxiety-like behavior, and effects of NP on the regulators (NMDAR2B, PSD-95, Synapsin1) expressions of synaptic plasticity in vivo and in vitro experiments. In vivo, 40 male SD rats were randomly divided into 4 groups (each with 10 rats): low dose (0.4 mg/kg/day, L-NP), middle-dose (4 mg/kg/day, M − NP), high-dose (40 mg/kg/day, H-NP) and corn oil (Control) groups. In vitro, HT22 cells were divided into a control group (Control), NP group (NP, 20 μM), glutamine acid receptor inhibitor group (MK-801, 10 μM) and MK-801 + NP group. The concentration of NP in the hippocampus rised with the increase of NP exposure concentration in the treatment groups ( F  = 7.542, P  = 0.001). Compared with the control group, the residence time in the dark box after NP exposure had extended ( F  = 117.927, P  < 0.01). The duration ( F  = 112.054, P  < 0.01) and the number of times ( F  = 13.514, P  < 0.01) to enter the closed arm in the NP exposure group significantly increased. There were more neurons degeneration and nuclear shrinkage in the M − and H– NP groups, while the average number of shrinked neurons increased with the increasing dose of NP exposure. The protein expressions of PSD-95 ( F  = 97.723, P  < 0.01), Synapsin1 ( F  = 41.797, P  < 0.01) and NMDAR2B ( F  = 3.440, P  = 0.036) in the NP group were lower than those of the control. Simultaneously, the expressions of PSD-95, Synapsin1 and NMDAR2B in the hippocampus were down-regulated; the mRNA expression of PSD-95 ( F  = 19.950, P  < 0.01), Synapsin1 ( F  = 3.498, P  = 0.035) and NMDAR2B ( F  = 9.293, P  < 0.01) genes in the hippocampus decreased in the M − and H-NP groups. In vitro, the trend of the fluorescence intensity expressed by PSD-95 ( F  = 2.606, P  = 0.124) and Synapsin1 ( F  = 20.573, P  < 0.01) among the groups was: MK-801 + NP group < MK-801 < NP group. The protein expressions of PSD-95 ( F  = 5.699, P  = 0.022), Synapsin1 ( F  = 10.820, P  = 0.003) and NMDAR2B ( F  = 6.041, P  = 0.019) were down-regulated. These results suggested that subchronic exposure to environmental concentrations of NP induced anxiety, and reduced the protein and/or mRNA expressions of regulators of synaptic plasticity (PSD-95, Synapsin1, NMDAR2B). Graphical abstract: Image 1 Highlights: NP exposure at environmental dose induced anxiety-like behavior. NP decreased the expressions of synapse-associated proteins. NMDA receptor inhibitor MK-801 could aggravate the toxic effects of NP.